Peningkatan Hasil Belajar PAI Menggunakan Model Make A Macth di Kelas V SDN 01 Bonjol - Susilawati, Dinia (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Education plays an important role in shaping the condition of a country, both economically and socially. One of the subjects that has a significant role is Islamic Religious Education, which aims to develop students’ potential comprehensively. However, in practice, the teaching methods used are still conventional and do not enhance student engagement, particularly in Islamic Religious Education classes. Therefore, this study aims to improve the learning outcomes of fifth-grade students at SDN 01 Bonjol by implementing the Make a Match learning model on the topic of Living in Peace and Harmony. This study focuses on improving student learning outcomes through a more interactive and enjoyable teaching method. The results of the study indicate that the application of the Make a Match model can significantly improve student learning outcomes, with an increase in active participation and student motivation during lessons.